1. Limited time only! Sign up for a free 30min personal tutor trial with Chegg Tutors
    Dismiss Notice
Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Homework Help: A square matrix A with ker(A^2)= ker (A^3)

  1. Sep 20, 2011 #1
    1. The problem statement, all variables and given/known data
    a square matrix A with ker(A^2)= ker (A^3), is ker(A^3)= ker (A^4),verify...

    2. Relevant equations

    3. The attempt at a solution
  2. jcsd
  3. Sep 20, 2011 #2
    What did you try already??
  4. Sep 20, 2011 #3
    it means that A^2*vector x= 0 and A*x=0 has same result,then I really confused how to do the next step
  5. Sep 20, 2011 #4
    No, it means that


    You need to prove that

  6. Sep 20, 2011 #5
    emm...., to the difinition it says that ker(A) is T(x)=A(x)=0
  7. Sep 20, 2011 #6
    Yes, but you're not working with ker(A) here, but with ker(A2).
  8. Sep 20, 2011 #7
    should define a matrix A and write A^2 as dot product of A & A,and also to A^3...it seems to be so complex, or use the block to devide the matrix into some small matrix?
  9. Sep 20, 2011 #8
    Do you understand my Post 4??
  10. Sep 20, 2011 #9
    so times A on both side of the equation?
  11. Sep 20, 2011 #10
    No, you need to prove two things:

    If [itex]A^3x=0[/itex], then [itex]A^4x=0[/itex]. This can indeed be accomplished by multiplying sides with A.

    But you also need to prove that if [itex]A^4x=0[/itex], then [itex]A^3x=0[/itex].
  12. Sep 26, 2011 #11
    so Ker (A^2)=0 can lead to Ker(A^4)=0,then?
  13. Sep 26, 2011 #12


    User Avatar
    Science Advisor

    NO ONE has said that Ker(A^2)= 0 so I do not understand why you are asking this question. You seem, frankly, to have no idea what the question is saying. ker(A^2)= ker(A^3) means, as micromass said, "A^2x= 0 if and only if A^3x= 0". You want to use that to prove "A^3x= 0 if and only if A^4x= 0". As micromass said, the first part is easy: if A^3x= 0 then, applying A to both sides, A^4x= A0= 0 which proves that ker(A^3) is a subset of ker(A^4). You still need to prove the other way: if A^4x= 0, then A^3= 0. You cannot just multiply by A^{-1} because you have no reason to think that A is invertible. But notice that ker(A^2)= ker(A^3) has not yet been used so it might help to note that A^4x= A^2(A^2x).
Share this great discussion with others via Reddit, Google+, Twitter, or Facebook